2023
DOI: 10.1038/s41598-023-32996-5
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and separation of Cs(I) and Ba(II) from aqueous solution using zinc ferrite-humic acid nanocomposite

Abstract: Reclaimable adsorbents have an essential role in removing radionuclides from waste streams. Herein, zinc ferrite-humic acid ZFO/HA nanocomposite was synthesized for effective cesium and barium adsorption. The prepared ZFO/HA nanocomposite was analyzed using analytical techniques including XRD, FTIR, EDX, and SEM. From kinetic studies, the mechanism adsorption process follows the second model. The isotherm studies clarified that the Langmuir model fit the adsorption of both ions onto the prepared sample, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Also, at around 3428 cm −1 , O–H stretching appears. Aromatic C=C stretching was determined to be responsible for the 1635 cm −1 absorption band [ 23 ], indicating that the cubic spinel phase was effectively manufactured for the CZ-FN nanostructures.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, at around 3428 cm −1 , O–H stretching appears. Aromatic C=C stretching was determined to be responsible for the 1635 cm −1 absorption band [ 23 ], indicating that the cubic spinel phase was effectively manufactured for the CZ-FN nanostructures.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The growth capacity of the adsorption process with increasing amounts of CZ-FN is predictable because as the quantity of CZ-FN rises, the active site numbers on the surface of CZ-FN increase [ 24 ]. There is an inconsistency between the removal efficiency of each ion and the amount of sorbent, and this clarifies that the functional group on the surface of CZ-FN has a marked preference for Sr (II) over Cs (I); this can be referring to increasing the hydration radius of Cs (I) comparing with Sr (II) [ 23 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesized composite (i.e., ZrP/MSP) exhibited excellent performance for Sr 2+ adsorption over a wide pH range and achieved a much faster adsorption equilibrium (90 min) and a higher maximum adsorption capacity (100.77 mg/g) than the bulk ZrP (i.e., 180 min for 68.88 mg/g) without grafting. Abdel Maksoud [ 16 ] synthesized a zinc ferrite and humic acid (ZFO/HA) nanocomposite material for the effective adsorption of cesium. Its monolayer capacity is 42.55 mg/g, and it was found that the adsorption reaction is a spontaneous endothermic reaction.…”
Section: Introductionmentioning
confidence: 99%